(untitled) - Raamachandran, J. (Chennai, India, 2000)
Boundary and Finite Elements Theory and Problems illuminates the various approximate methods used in solving structural mechanics problems. Rather than delving deep into the mathematics, it focuses on imparting a working knowledge of the methods. Organized into three main sections, the author explores approximate methods, including the variational, Rayleigh-Ritz, finite difference and weighted residual methods, the finite element method, and the boundary element method.
Keywords: Boundary value problems,Finite element method